Kajian Nilai Gizi Ikan Tongkol (Euthynnus Affinis) Dengan Pengawet Asap Cair Dari Tempurung Kelapa - Mautuka, Zakarais Adrianto; Banik, Yovita N.; Botahala, Lot (Jurnal Ilmiah Wahana Pendidikan, 2026)
The use of liquid smoke in processing smoked fish is an alternative to improve quality and reduce air pollution resulting from the traditional smoking process. This study aims to determine the effect of providing grade-1 coconut shelled liquid smoke on the nutritional value of tuna that hasbeen preserved using 3 treatments with a storage period of one month. The results showed that the concentration of liquid smoke had an effect on the nutritional value of fish (water, fat, ash, protein and carbohydrate content) in the three treatments. Liquid smoked tuna with spices added with water content of 54.12%, fat content of 11.50%, protein content of 25.82%, ash content of 2.55%, 1.01%. Liquid smoked tuna with a water content of 46.79%, fat content of 10.93%, protein content of 30.20%, ash content of 4.11%, carbohydratecontent of 2.31%. Tuna (salting) fish with water content 52.28%, fat content 8.43%, protein content 30.62%, ash content 4.07%, carbohydrate content 0.48%.